Experimental study on the anti-fouling effects of EDM machined hierarchical micro/nano structure for heat transfer surface. (5th November 2019) - He, Z.R.; Liu, C.S.; Gao, H.Y.; Jie, X.H.; Lian, W.Q.
Highlights: Hierarchical micro/nano structure (HMNS) was prepared by EDM method. HMNS inhibits the adhesion and corrosion of fouling. The fouling resistance of HMNS was lower than the polished surface. The HMNS extends the fouling induction period at least 140%. The HMNS enhances the pool boiling heat transfer performance significantly. Abstract: Fouling is a common and serious problem for the heat exchanger, which leads to the high energy consumption, corrosion and other harms. Hence, a hierarchical micro/nano structure is designed and fabricated on the copper heat exchange surface by electrical discharge machining to improve the anti-fouling property and address the fouling problem. The surface characteristics and anticorrosion property were respectively investigated by using scanning electron microscope and energy dispersive spectrometer, contact angle measuring instrument, surface roughness measurement and electrochemical workstation. The anti-fouling experiment and pool boiling heat transfer experiment were carried out by self-made heat transfer property test device. Results show that the electrical discharge machining modified surface is characterized with hierarchical micro/nano structures, exhibiting superior anticorrosion and anti-fouling properties, which is attributed to its hydrophobic surface. The anti-fouling property, fouling induction period and contact angle values of the hierarchical micro/nano structure are increase with the increasing electrical discharge machining currents. Compared with the polished surface, the hierarchical micro/nano structure extends the induction period from 220% to 453.3% in heat flux of 88 kW·m −2 and from 140% to 360% in heat flux of 154 kW·m −2 . In the heat flux of 254 kW·m −2, the induction period of hierarchical micro/nano structure is disappear. Besides, the hierarchical micro/nano structure displays a higher critical heat flux and a much higher heat transfer coefficient of 214.6% than that of 62.9% for the polished sample. This study provides a novel method for fabricating anti-fouling surface with enhanced pool boiling and promotes the application prospect of electrical discharge machining method.